Komik Digital Sebagai Strategi Bisnis Media Online Olahraga: Studi Pada Gorilasport.Com - Fandi Akbar Saputra; Suluh Gembyeng Ciptadi (CoverAge: Journal of Strategic Communication, 2019)
The online media industry is growing rapidly now. The presence of various types of online media is coloring competition in the media industry. Media business is a gap to find a background that is the principle of a news portal. Gorilasport.com is a news portal that provides information about sports with the main content of digital comics. They use digital comics as the main content in presenting news that can be seen on a news portal. So, this research aims to analyze digital comic in online media business in Indonesia by sports news portal Gorilasport.com. This study uses the post-positivist paradigm with a qualitative approach and the type of research is descriptive. The unit of analysis is Gorilasport.com media organization. The concept used is the strategy of media business, digital comics and online sports media with the help of previous research studies. Data collection techniques were carried out with interviews and documentation. The data analysis technique uses the Miles and Huberman models. To test the validity of the data the researcher used source triangulation. The results show that media businesses using digital comic. The advantage gained is that this business can continue without content presentation, is liked by the public and is not easily boring.